Simulation of Supersonic Flow in an Ejector Diffuser Using the JPVM - Carlos Couder-Castañeda (Journal of Applied Mathematics)
The ejectors are used commonly to extract gases in the petroleum industry where it is not possible to use an electric bomb due the explosion risk because the gases are flammable. The steam ejector is important in creating and holding a vacuum system. The goal of this job is to develop an object oriented parallel numerical code to investigate the unsteady behavior of the supersonic flow in the ejector diffuser to have an efficient computational tool that allows modeling different diffuser designs. The first step is the construction of a proper transformation of the solution space to generate a computational regular space to apply an explicit scheme. The second step, consists in developing the numerical code with an-object-oriented parallel methodology. Finally, the results obtained about the flux are satisfactory compared with the physical sensors, and the parallel paradigm used not only reduces the computational time but also shows a better maintainability, reusability, and extensibility accuracy of the code.